PENGARUH MENCARI VARIASI, KETIDAKPUASAN DAN KETIDAK TERSEDIAAN PRODUK TERHADAP PERPINDAHAN MEREK - Dessy Yunita; Aslamia Rosa (Program Studi Magister Manajemen FE Unsri, 2016)
This study aims to determine the effect variety seeking, dissatisfaction of previous product, and the unavailability of products to brand switching. The sampling method is using the Non-Probability Sampling with purposive sampling technique. This study took a sample of 100 female students who ever make the switch from local brands to import brands. Methods of data analysis is using multiple linear regression. The results show the effect of variable X2 is dissatisfaction have the greatest influence in the amount of 27.9% of the variable displacement of the brand in the appeal seek variety and unavailability of products. The limitations in this research are (1) Factors of dissatisfaction can give a negative impact to the company; because consumers can give a negative experience had to be told to others with or without asking; (2) The company must have a quality standard to prevent of dissatisfaction. Implication in marketing discussed